Особливості жирнокислотного спектра ліпопротеїнів високої щільності у пацієнтів з метаболічним синдромом - Лизогуб, В. Г.; Волошина, О.О.; Брюзгіна, Т.С.; Лизогуб, Г.В.; Бондарчук, О.М.; Левіщенко, О.С. (Видавничий дім "Академперіодика" НАН України, 2007)
We study the particular features of the composition of blood serum fatty acids (FA) of high density lipoproteins (HDL) in patients with metabolic syndrome (MS) (39.7 ± 3.4 years). In patients with MS, as compared with healthy adults of the same age, an increase of saturated FA and a signiﬁcant decrease of unsaturated and polyunsaturated FA are revealed. The signiﬁcant correlation is revealed between indices of abdominal adiposity, intima media thickness of arteria carotis communis, and level of some FA in HDLs. This change of the FA composition could be a cause of decreasing the HDL antiatherogenic capacity.